"Natural environment and constitution of India / by P. R. Trivedi, Piare Lal Sharma [and] K. N. Sudarshan" - "Trivedi, P. R." (New Delhi, 1994)
This book has been an attempt to keep pace with continuing rapid developments in the field of Natural Environment during the last twenty five years. The basic aim of the book is to present in a rigorous, quantitative manner many of the neces sary fundamentals needed for the analysis of Natural Environment.
Keywords: Environmental law